The String of Nodes - Leonardo Gioia (Master's Programs in International Relations, Faculty of Social and Political Science, Jenderal Achmad Yani University (UNJANI)., 2026)
The Indo-Pacific region handles 60% of global maritime trade, and control over its territories is contested in strategic doctrine and public debate. Yet the focus on military primacy, alliances, and institutions such as ASEAN often bypasses a fundamental question: how are these exchanges materialised? Politics, economics and strategy converge in an under-theorized element: logistics. Without railways, ports, pipelines, and digital supply-chain platforms, there is no trade, integration, or durable influence. This article introduces logistical power as the capacity to project influence through infrastructure networks that bind economies, shape dependencies, and reconfigure geopolitical space. Moving beyond